Effects of the Rate of Interest and Productivity Growth on the Output Growth - Anglinov, Sergey (Université d'Ottawa | University of Ottawa, 2004)
This paper studies the effect of the real rate of interest and productivity growth on output growth. It contrasts the views of mainstream economists and post-Keynesian economists on the problem. A survey of literature related to these two schools of thoug